Investigation of Alcohol Factor Influence in Quantitative Descriptive Analysis and in the Time-Intensity Profile of Alcoholic and Non-Alcoholic Commercial Pilsen Beers Samples - Juliana A. Paixão; Elson Tavares Filho; Helena Maria André Bolini (Beverages, 2020)
In recent years, non-alcoholic beers have presented a growth considered satisfactory and exciting for the brewing industry. Such growth is allied to a change in the consumer profile, in addition to changes in traffic laws. However, the consumer seeks a product considered healthier, but as tasty as the original. Thus, this study aimed to identify the influence of the alcoholic factor in sensory profile, through quantitative descriptive analysis and time intensity analysis of Pilsen beer samples. An acceptance test with 120 consumers of beer was performed. A quantitative descriptive analysis was carried out by 11 trained assessors to determine the sensory profile of beers. For identification of influences of alcohol factor in the dynamic profile of alcoholic flavor and bitter taste the time-intensity analysis were realized. The results demonstrate that alcohol factor influences both the quantitative descriptive profile and dynamic profile, in addition the correlations between the quantitative descriptive analysis (QDA®) and hedonic data show that the alcoholic flavor and the alcoholic aroma are attributes that contribute positively to acceptance of samples. In view of the results, studies such as the present are of great importance for the improvement of product quality, directly reflecting a greater acceptance of beer consumers.